Laser-Induced photothermal activation of multilayer MoS2 with spatially controlled catalytic activity; Journal of Colloid and Interface Science; Vol. 654, Pt. A - Tran Tuan Hoang; Rodriguez (Rodriges) Contreras R. D. Raul David; Villa Pineda N. E. Nelson Enrrique; Shchadenko S. V. Sergey Vladimirovich; Averkiev A. A. Andrey Alekseevich; Hou Yang; Zhang Tao; Matkovic A. Aleksandar; Sheremet E. S. Evgeniya Sergeevna (2024, 2024)
Title screen